Expanding the function (1+e^x) into power series in terms of the Dirichlet eta function and the Stirling numbers of the second kind - Li, Wen-Hui; Lim, Dongkyu; Qi, Feng (Carpathian Mathematical Publications, 2024)
In the paper, using several approaches, the authors expand the composite function (1+e^x) into power series around x=0, whose coefficients are expressed in terms of the Dirichlet eta function η(1-n) and the Stirling numbers of the second kind S(n,k).